2008
DOI: 10.1007/s12253-008-9119-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TGFβ1 and Its Signaling Components by Peripheral Lymphocytes in Systemic Lupus Erythematosus

Abstract: Transforming growth factor beta1 (TGFbeta1) is an important immunosuppressive cytokine. Defects in its production by lymphocytes and the failure of TGFbeta1 to regulate immunological functions have been described in SLE. Expression of TGFbeta1 and the related signaling pathway was studied in the peripheral lymphocytes of SLE patients. The total plasma TGFbeta1 level in active and inactive SLE patients compared to healthy controls was also measured. TGFbeta1 and all downstream signaling elements were expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Our study found that TGF-β induced generation of CD4 + CD25 high FoxP3 + T cells in HCs, whereas this was not seen in SLE patients. This finding is consistent with a previous study that demonstrated defective expression of TGF-β signal transduction molecules in most SLE patients [40]. Interestingly, we found that the addition of CD200Fc rescued the defective generation of CD4 + CD25 high FoxP3 + T cells in SLE patients, indicating that CD200 could intervene in the TGF-β signaling pathway and promote Treg generation.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that TGF-β induced generation of CD4 + CD25 high FoxP3 + T cells in HCs, whereas this was not seen in SLE patients. This finding is consistent with a previous study that demonstrated defective expression of TGF-β signal transduction molecules in most SLE patients [40]. Interestingly, we found that the addition of CD200Fc rescued the defective generation of CD4 + CD25 high FoxP3 + T cells in SLE patients, indicating that CD200 could intervene in the TGF-β signaling pathway and promote Treg generation.…”
Section: Discussionsupporting
confidence: 93%
“…TGF␤1 is mainly expressed in association with membrane vesicles (41), including vesicular structures of higher density than exosomes (42). Although a relative deficiency of TGF␤1 was previously demonstrated in T lymphocytes from SLE patients, circulating levels were increased (43). Such an increase has not been consistently demonstrated (44).…”
Section: Discussionmentioning
confidence: 93%
“…TGF-b is a fibrotic cytokine involved in wound healing, angiogenesis and formation of scar tissue. Plasma levels of TGF-b were significantly elevated in both inactive and active SLE patients compared with controls; however, TGF-mRNA from SLE lymphocytes was greatly reduced or absent [133]. A study evaluating microparticle proteins found that TGF-b was reduced in SLE, which the authors surmise is related to reduction of platelets, a key producer of TGF-b [134].…”
Section: Tgf-mentioning
confidence: 99%